Effect of epidural analgesia on the duration of labour and pains: a comparative study - Chauhan, Pallavi; Shirodkar, S. D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Epidural analgesia is regional anaesthesia that blocks pain in a particular region of the body. The use of Epidural Analgesia (EA) in labor is widespread in modern labor ward practice, and its benefits in terms of pain relief are well-recognized. Objective of this study was to study the effect of epidural analgesia on the duration of labour and pains. Methods: The present study was conducted on 60 women in the department of obstetrics and gynecology at Topiwala National Medical College, Mumbai during a period from October 2014 to January 2017. The women requesting EA were assigned as the study group (Group A - 30 cases) and women not receiving EA were included in the control group (Group B - 30 cases). Results: The duration of active phase of first and second stage of labour was found to be prolonged in patients who received EA as compared to control group. An increase in number of caesarean sections and requirement of oxytocin augmentation was found to be more in Group A as compared to Group B. There was no statistically significant difference in Apgar score of newborns at 1 min and 5 min in both the groups. The patients demanding epidural drug had better pain relief during labour. In Group A, 17% of patients and in Group B, 7% of patients had nausea and vomiting. Other side effects were minimal. Conclusions: Epidural analgesia is not a totally free of disadvantages, it is the most effective mode of pain relief available compared with other techniques. The addition of patient-controlled epidural analgesia and innovations using new technologies enhance patient satisfaction.